Smart Composites and Processing - Kim, Kwang-Jea (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue covers manufacturing of a smart polymer composites via choice of ingredients, such as polymer, filler, and additives, as well as their unique composition. It also covers the smart processing of polymer composites, which is influenced by the choice of mixers, processing condition, processing technique, etc.